2022
DOI: 10.3389/fimmu.2022.1051008
|View full text |Cite
|
Sign up to set email alerts
|

The immune response to lumpy skin disease virus in cattle is influenced by inoculation route

Abstract: Lumpy skin disease virus (LSDV) causes severe disease in cattle and water buffalo and is transmitted by hematophagous arthropod vectors. Detailed information of the adaptive and innate immune response to LSDV is limited, hampering the development of tools to control the disease. This study provides an in-depth analysis of the immune responses of calves experimentally inoculated with LSDV via either needle-inoculation or arthropod-inoculation using virus-positive Stomoxys calcitrans and Aedes aegypti vectors. S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…A number of other poxviruses are also transmitted by blood-feeding vectors including the leporipoxviruses myxoma virus (13, 14) and Shope fibroma virus (15, 16), the avipoxvirus fowlpox virus (17, 18), and the capripoxviruses goatpox virus and sheeppox virus (19, 20). LSDV has been transmitted from a clinical to naïve animal under experimental conditions by Aedes aegypti mosquitoes (21, 22), Amblyomma hebraeum and Rhipicephalus appendiculatus ticks (23, 24), and S. calcitrans flies (22, 25, 26). LSDV can be acquired from cutaneous nodules by a range of insect species, then retained on the vector mouthparts for days before being deposited in a recipient animal (27, 28).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of other poxviruses are also transmitted by blood-feeding vectors including the leporipoxviruses myxoma virus (13, 14) and Shope fibroma virus (15, 16), the avipoxvirus fowlpox virus (17, 18), and the capripoxviruses goatpox virus and sheeppox virus (19, 20). LSDV has been transmitted from a clinical to naïve animal under experimental conditions by Aedes aegypti mosquitoes (21, 22), Amblyomma hebraeum and Rhipicephalus appendiculatus ticks (23, 24), and S. calcitrans flies (22, 25, 26). LSDV can be acquired from cutaneous nodules by a range of insect species, then retained on the vector mouthparts for days before being deposited in a recipient animal (27, 28).…”
Section: Introductionmentioning
confidence: 99%
“…They are also suspected to be carriers of Rift Valley fever virus (50) and bovine herpes virus (51). S. calcitrans have also been proposed as vectors of LSDV (22, 25, 26, 27, 52, 53).…”
Section: Introductionmentioning
confidence: 99%
“…Next, we hypothesized a link between miR-29a expression and CD8+ T cell activation and proliferation following LSDV exposure in cattle. There are few publications on the CMI response to LSDV infection [ 42 , 57–59 ] and the information pertaining to the CMI response to LSDV is very limited. Therefore, we first provided insights into CMI by analysing the PBMCs of cattle recovered from LSDV infection in the field.…”
Section: Discussionmentioning
confidence: 99%
“…(2022) ( 91 ) following LAV vaccination, many other studies have reported that Nabs were not sufficient for protection following vaccination, for example, with subunit vaccines ( Table 1 ) ( 198 , 199 ). Similarly, while Nabs can protect cattle against LSDV infection, Nabs are not a reliable indicator of protection following vaccination against LSDV as not all vaccinated animals that are fully protected against LSDV seroconvert ( 10 , 11 ) ( Table 1 ). This highlights the risk of assessing Nab titers as the sole CoP in all contexts.…”
Section: Humoral Immune Features As Correlates Of Protectionmentioning
confidence: 99%
“…Intriguingly, unlike the other viruses discussed in this review where Nabs—to homologous strains—are likely to be the primary CoP, CMI appears to be the primary CoP for ASFV ( Table 1 ) ( 89 , 218 , 219 ). Following vaccination against LSDV, T-cell responses increase; however, the functional role of these cells is yet to be studied ( 9 , 11 ). The importance of CD8+ T cells in protection from ASFV was highlighted through depletion of CD8+ cells (T cells and NK cells) from pigs immunized against ASFV, resulting in complete loss of protection in these pigs to ASFV challenge, compared to total protection observed in pigs immunized with CD8+ cells ( 92 ).…”
Section: Cellular Immune Features As Correlates Of Protectionmentioning
confidence: 99%